Serum Prolidase Activity, Oxidant and Antioxidant Status in Nonulcer Dyspepsia and Healthy Volunteers. (29th October 2013) - Kumari, Shweta; Verma, Akhilesh Kumar; Rungta, Sumit; Mitra, Rahul; Srivastava, Ragini; Kumar, Narender
Abstract : Helicobacter pylori (H. pylori) infection is associated with increased oxidative stress and serum prolidase activity (SPA) in many diseases. We aimed to observe SPA and oxidative stress in nonulcer dyspepsia (NUD) infected with and without H. pylori among eastern Indians. 106 patients with H. pylori positive NUD, 82 patients with H. pylori negative NUD, and 50 healthy individuals were selected. SPA, total antioxidant capacity (TAOC), and total oxidant status (TOS) were measured with the use of spectrophotometer and an automated measurement method. SPA, TOS, and oxidative stress index (OSI) were significantly higher in patients with H. pylori positive than H. pylori negative NUD and healthy individuals (all P < 0.0001 ), whereas TAOC was significantly lower (P < 0.0001 ). Nonsignificant, increased SPA (P value = 0.6083) and decreased TAOC (P value = 0.1186) were observed in patients with H. pylori negative NUD than healthy individuals, while increased TOS and OSI were significant (P < 0.0001 ). Weak, nonsignificant correlations were observed between serum prolidase activity and TAOC, TOS, and OSI in H. pylori positive cases. Thus, increased SPA along with increased oxidative stress was observed, which seem to be closely associated with H. pylori infection. SPA and oxidative stress seem to be used as biomarkers for H. pylori infection in NUD.